architecture from 'Les Plages de France. Texte et dessins par Bertall'. - Auteur inconnu... (The British Library, 1882)
Notice issue d Europeana. This image has been taken from scan 000413 from "Les Plages de France. Texte et dessins par Bertall". The title and subject terms of this image have been generated from tags, created by users of the British Library's flickr photostream.
http://creativecommons.org/publicdomain/mark/1.0/
Keywords: europeana; image; patrimoine europeen; Bibliothèque numerique; iconographie